Immovable cultural heritage in the context of new localism - Uršič, Matjaž (Družboslovne razprave, 2023)
On the declarative level, immovable (physical) cultural heritage is a convenient subject of a variety of programmes, conservation approaches and legislative processes supposedly tied to sustainability development plans. The declarativeness of immovable cultural heritage integration processes is often exposed in spatial antagonisms based on frictions between local communities on one side and, on the other, conservation approaches, the development aspirations of investors, political structures and other actors who seek to assert their particular interests and needs. The paper analyses the mentioned frictions through the prism of “new localism” trends and connects them to the findings of several Slovenian case studies.
Keywords: Kulturna dediščina; lokalizem; novi lokalizem; participacija; prostorska dediščina; Regionalizem; trajnostni razvoj